Mutual acoustic impedance of circular sources with parabolic vibration velocity distribution for high frequencies - LENIOWSKA, L.; RDZANEK, W.; WITKOWSKI, P. (Archives of Acoustics, 1992)
In the paper the mutual impedance of circular planar sources with parabolic vibration velocity distribution occurring harmoniously in time is analyzed. It is assumed that the sources set in planar rigid baffle radiate into a lossless and homogeneous gas medium. The acoustic impedance is calculated using the method based on the Fourier representation of acoustic pressure, thanks to which the mutual impedance is expressed in the Hankel representation. The real integrals in the formula are replaced by complex ones and integrates is performed round a closed and smooth integration contour. Using approximation methods, the expression for mutual impedance at high frequencies is obtained.